Biochemical correlation of serum insulin, high-sensitivity C reactive protein and lipid tetrad index with thyroid-stimulating hormone levels in patients with hypothyroidism - Jamatia, Mandayal; Sharma, Avdhesh Kumar; Charak, Rimpy (International Journal of Research in Medical Sciences, 2026)
Background: Hypothyroidism is a prevalent endocrine disorder associated with insulin resistance, dyslipidemia, chronic low-grade inflammation, and an increased risk of cardiovascular disease. Thyroid hormone deficiency adversely affects glucose and lipid metabolism, contributing to metabolic dysfunction. This study investigated the relationship between thyroid-stimulating hormone (TSH) levels and markers of insulin resistance, systemic inflammation, and atherogenic risk in patients with hypothyroidism. Methods: A hospital-based cross-sectional analytical study was conducted among 70 patients with hypothyroidism attending a tertiary care teaching hospital in Indore, Madhya Pradesh, India. Based on thyroid function tests, participants were categorized as having overt or subclinical hypothyroidism. Serum triiodothyronine (T3), thyroxine (T4), TSH, fasting insulin, high-sensitivity C-reactive protein (hs-CRP), and lipid profile were measured using standard laboratory methods. Insulin resistance was assessed using the homeostatic model assessment for insulin resistance (HOMA-IR), while atherogenic risk was evaluated using the lipid tetrad index (LTI). Correlation analysis was performed to examine associations between TSH and study variables. Results: Serum TSH demonstrated significant positive correlations with fasting insulin (r=0.42, p<0.01), hs-CRP (r=0.38, p<0.01), and LTI (r=0.44, p<0.001). Compared with patients with subclinical hypothyroidism, those with overt hypothyroidism had significantly higher fasting insulin, HOMA-IR, hs-CRP, and LTI values. Insulin resistance was identified in 58.6% of participants. Conclusions: Higher TSH levels are associated with insulin resistance, systemic inflammation, and increased atherogenic risk in hypothyroidism. These findings highlight the importance of comprehensive metabolic assessment for improved cardiovascular risk stratification and timely clinical intervention.